ChemInform Abstract: The Pauson—Khand Reaction of Medium Sized trans‐Cycloalkenes. Issue 28 (21st June 2013) - Lledo, Agusti; Fuster, Aida; Reves, Marc; Verdaguer, Xavier; Riera, Antoni
Abstract Starting carbonyl dicobalt complexes are readily prepared from Co2(CO)8 and the respective alkynes.